2021
DOI: 10.3171/2020.6.jns201296
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of incidentally discovered low-grade gliomas

Abstract: OBJECTIVEAlthough most patients with low-grade glioma (LGG) present after a seizure, a small proportion is diagnosed after neuroimaging is performed for a sign or symptom unrelated to the tumor. While these tumors invariably grow, some surgeons argue for a watchful waiting approach. Here, the authors report on their experience in the surgical treatment of patients with incidental LGG (iLGG) and describe the neurological outcomes, survival, and complications.METHODSRelevant cases were identified from a prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…Patients with a lesion consistent with incidental LGG should receive surgical resection, given the significant survival benefit associated with early surgery. 42 , 43 …”
Section: Discussionmentioning
confidence: 99%
“…Patients with a lesion consistent with incidental LGG should receive surgical resection, given the significant survival benefit associated with early surgery. 42 , 43 …”
Section: Discussionmentioning
confidence: 99%
“…In a large case series by Gogos et al GTR was achieved in 57% of incidental and 24% of symptomatic aLGGs, with a significantly shorter survival of symptomatic aLGGs (median 14.6 years) [54]. For adults, early resection resulted in a longer OS than observation and a delayed resection of aLGG [54]. To achieve a complete resection with the total removal of FLAIR abnormalities in aLGG is difficult, as the tumor is non-enhancing and often presents as normal tissue during surgery [7].…”
Section: Treatment Of Plgg Vs Algg 41 Surgerymentioning
confidence: 93%
“…In adults, GTR is more likely to be achieved in incidental lesions than in symptomatic lesions, which is most probably due to their non-eloquent location. In a large case series by Gogos et al GTR was achieved in 57% of incidental and 24% of symptomatic aLGGs, with a significantly shorter survival of symptomatic aLGGs (median 14.6 years) [54]. For adults, early resection resulted in a longer OS than observation and a delayed resection of aLGG [54].…”
Section: Treatment Of Plgg Vs Algg 41 Surgerymentioning
confidence: 96%
See 1 more Smart Citation
“…In a series of 143 gliomas, Pallud et al noted an inverse correlation between radiographic growth rates and survival, advocating for this parameter’s incorporation into treatment planning [ 35 ]. Additionally, iLGGs demonstrate a median Ki67 proliferative index of 5.0% [ 7 , 15 ], which is comparable to that of symptomatic LGGs, indicating that early surgical resection may be beneficial to improve prognosis and survival outcomes [ 7 , 15 , 36 ]. Gogos et al reported a key finding that 13% of iLGGs were observed to have IDH1/IDH2 wild-type genetic features which are associated with a worse prognosis, however, this information would not have been revealed if treatment had been delayed [ 36 ].…”
Section: Methodsmentioning
confidence: 99%